FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN KESEHATAN OLEH PEMULUNG DI TPA KELURAHAN SUMURBATU KECAMATAN BANTARGEBANG KOTA BEKASI TAHUN 2020 - Dhea Julia Lestari, (2021)
Scavengers are people who have a high risk of exposure to diseases due to unhealthy environmental conditions. The purpose of this study was to determine the description and relationship between the characteristics of scavengers, the characteristics of health services and the utilization of health services by scavengers in the landfill area of Sumurbatu Village in 2020. The quantitative research method with cross-sectional design used random sampling techniques. The number of samples was 150 families in the landfill area of Sumurbatu Village. Measuring instrument in the form of a questionnaire with data collection techniques in the interviews form. Data analysis used chi-square analysis and multiple logistic regression analysis. The results showed that the variables related to the utilization of health services were knowledge variable (p = 0.001), number of families (p = 0.021), perception of pain (p = 0.001), and family support (p = 0.030). As well as the dominant variable related to the utilization of health services, that is knowledge (p = 0.000) with OR 12.876. It is hope that primary health care and health workers can involve more scavenger groups and communities around the landfill area in their work programs, such as providing health information.